Association of Serum C‐Reactive Protein Levels With Lupus Disease Activity in the Absence of Measurable Interferon‐α and a C‐Reactive Protein Gene Variant. Issue 6 (June 2014) - Enocsson, Helena; Sjöwall, Christopher; Kastbom, Alf; Skogh, Thomas; Eloranta, Maija‐Leena; Rönnblom, Lars; Wetterö, Jonas
<x xml:space="preserve">Abstract</x> Objective The type I interferon (IFN) system is important in the pathogenesis of systemic lupus erythematosus (SLE). We previously demonstrated an inhibitory effect of IFNα on interleukin‐6 (IL‐6)–induced C‐reactive protein (CRP) in vitro, hypothetically explaining the poor correlation between disease activity and CRP levels in SLE. This study was undertaken to investigate disease activity, IL‐6 levels, and CRP levels in relation to a CRP gene polymorphism and IFNα. Methods Sera from 155 SLE patients and 100 controls were analyzed for CRP. Patients were genotyped for a CRP single‐nucleotide polymorphism (rs1205) associated with low CRP levels. Serum IFNα and IL‐6 levels were quantified by immunoassays. Clinical disease activity was assessed using the SLE Disease Activity Index 2000 (SLEDAI‐2K). Results CRP levels were increased in SLE patients compared to controls, but were not associated with SLEDAI‐2K or IL‐6 levels. However, exclusion of patients carrying at least one rs1205 minor allele revealed an association between disease activity and CRP levels (P = 0.005). We found a strong association between disease activity and CRP levels (P < 0.0005) when patients with measurable IFNα levels as well as the minor allele of rs1205 were excluded from the analysis. Similarly, when patients with elevated IFNα levels and/or the rs1205 polymorphism were excluded, IL‐6 levels were associated with CRP levels. Conclusion The present study demonstrates that the serum IFNα level as well as the CRP genotype affect the CRP response in SLE patients. Lack of correlation between serum levels of CRP and disease activity could therefore be explained by activation of the type I IFN system and polymorphisms in the CRP gene.